2012
DOI: 10.1524/zpch.2012.0238
|View full text |Cite
|
Sign up to set email alerts
|

On Ligand Binding Energies in Porphyrinic Systems

Abstract: Porphyrins / Phthalocyanins / Energy Decomposition Analysis / Bond Properties / Solvent-Metal Complexation / Metal CoordinationEnergy decomposition analysis is a powerful tool to study the bond properties of molecules. Here, we used a recent implementation by P. Su and H. Li (J. Chem. Phys. 131 (2009) 014102) to test the method for investigations of ligand binding to medium sized molecules (30-40 atoms). We studied the properties of the bond between porphyrins or phthalocyanines with central metals without (Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The CdTPP spectra in anhydrous toluene and THF showed only a very small bathochromic shift of the two Q bands from λ =568 to 573 nm and from λ =609 to 615 nm, respectively, which we assigned to a solvatochromic effect (see Figure S5). For MgTPP, especially in THF, five‐coordinated species should be prevalent, in addition to the six‐coordinated one 13. A four‐coordinated Mg species within porphyrins and (bacterio)chlorophylls has never been encountered experimentally in crystal structures owing to them being unstable and coordinatively unsaturated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CdTPP spectra in anhydrous toluene and THF showed only a very small bathochromic shift of the two Q bands from λ =568 to 573 nm and from λ =609 to 615 nm, respectively, which we assigned to a solvatochromic effect (see Figure S5). For MgTPP, especially in THF, five‐coordinated species should be prevalent, in addition to the six‐coordinated one 13. A four‐coordinated Mg species within porphyrins and (bacterio)chlorophylls has never been encountered experimentally in crystal structures owing to them being unstable and coordinatively unsaturated.…”
Section: Methodsmentioning
confidence: 99%
“…Its symmetry is supposed to be close to D 4 h . However, in the minimum energy geometry, the four peripheral phenyl rings are known to be twisted by 65–70° with respect to the porphyrin skeleton;1013 this lowers the symmetry to C 2 v . In coordinating solvents, magnesium atoms in chlorophylls or porphyrins become five‐ or even sixfold coordinated, which reduces the symmetry further.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, iron porphine maintained its sensitivity for most of the measured gases, owing to its two strong axial coordination sites. These different behaviors between zinc and iron porphines can be supported by two separate studies by Schalk [ 35 ] and Kang [ 42 ]. They calculated the binding energies of water molecules to zinc and iron porphyrinic systems and showed that zinc porphine has a higher affinity to water molecules than that of iron porphine.…”
Section: Resultsmentioning
confidence: 69%
“…However, it can be seen from Figure 4 that the intensity ratio slightly deviated from 1.0, reflecting the altered porphine-gas interaction by zinc insertion. Zinc porphine generally had a strong pentadentate coordination mode, which allowed one axial ligand to be complexed to the central zinc atom [ 35 ]. When two ligands were coordinated to the zinc center, zinc porphine showed a six-coordinated structure with two axial ligands, in which the binding energy of a second complexation was much lower than that of the first [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…An anisotropy of 0.1 for SE represents the dephased case, which is reasonable to assume since we do not observe any fast components which might be due to the distorted shape of CdTPP as compared with the highly symmetric MgTPP. 33 Now consider ESA as being wavelength independent and having a fixed value of r ESA . Moreover, define …”
Section: B Modeling Anisotropy Datamentioning
confidence: 99%